Risk of convulsive epilepsy following acute seizures in Kenyan children. Issue 3 (31st August 2016) - Bistervels, Ingrid M.; Kariuki, Symon M.; Newton, Charles R. J. C.
Summary: Objective: The prevalence of epilepsy is high in Africa, and people with epilepsy often have a history of acute seizures. We determined whether acute seizures are associated with risk for epilepsy in rural Africa, where both conditions are common and may have shared risk factors. Methods: A total of 16, 438 children (2, 991 with acute seizures and 13, 447 without seizures) admitted to Kilifi County Hospital from 2002 to 2008 were followed up with epidemiological surveys conducted in 2003 and 2008 to assess the prevalence of epilepsy and the associated risk factors. Cox proportional hazards regression models were used to identify the risk factors. Prevalence ratios were computed using log binomial regression models. Results: The prevalence of epilepsy was higher in admissions with acute seizures (5.0% [95% confidence interval (CI), 4.3–5.9%]) than in those without seizures (0.7% [95% CI, 0.5–0.8%]), p < 0.0001). Acute seizures were associated with epilepsy after accounting for potential confounders in a Cox regression model (hazard ratio [HR] = 1.53 [95% CI, 1.10–2.14]). Prevalence was greater in complex acute seizures (5.9%; prevalence ratio [PR] = 1.58 [95% CI, 1.13–2.20]) or status epilepticus (7.5%; PR = 1.96 [95% CI, 1.32–2.91]) than in simple acute seizures (3.7%). Factors independently associated with epilepsy following acute seizures in Cox regression models were perinatal complications (HR = 3.60 [95% CI, 1.89–6.87]), cerebral palsy (HR = 1491.51 [95% CI, 144.30–15, 416.21]), duration of follow‐up (HR = 1.21 [95% CI, 1.09–1.35]), and malnutrition (relative risk [RR] = 0.24 [95% CI, 0.08–0.69]). Significance: Acute seizures in children are associated with subsequent risk for epilepsy that is greater than in the general population. The burden of epilepsy may be reduced by control of causes of acute seizures.